Myths and Systems: A Response to "'He Needs to Talk!': A Chaplain's Case Study of Nonreligious Spiritual Care". Issue 1 (2nd January 2016) - Hess, Denise
Abstract : In response to Chaplain Steve Nolan's case study, "He Needs to Talk: A Chaplain's Case Study of Nonreligious Spiritual Care, " this article presents two areas for further examination: the concept of the idealized "good death" and Bowen family systems theory as a model of psychospiritual care for the family system. Chaplains are challenged to critically engage the predominant and often romanticized views of the ideal death in order to support patients and their loved ones through difficult deaths such as the one depicted in this case study. Utilizing Bowen's concept of triangles and the family genogram intervention, chaplains are encouraged to provide care encompassing their full scope of practice as psychospiritual caregivers for the entire family system.